Arpazia: ilustrando uma obra autora - Almeida, Isabela Aparecida de Sousa [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
Considering the great number of works where text and image are related in the most varied ways, and particularly addressing the child and youth content, manifested, for example, in pop-up books, illustrated books and books with illustrations, among others, this project intends to carry out a series of watercolor illustrations based on an authorial fiction narrative of the fantasy genre, with the purpose of concluding a personal project that concerns two aspects of the author's poetics, thus discussing her creative process as an illustrator-writer using as reference, great illustrators and writers and adding to this the personal development for the image creation and characterization of the work in question, named Arpazia. Such accomplishment will be possible through a series of studies and technical experiments, aiming to obtain a concise and characteristic series to the book, which will be introduced in the final work in the future, resulting in a book with illustrations, one of the most traditional manifestations of children's book.

Tendo em vista o grande número de obras onde texto e imagem se relacionam nas mais variadas formas, abordando em especial o conteúdo infantojuvenil, que se manifesta, por exemplo, nos livros pop up, livros ilustrados, livros com ilustrações, entre outros, este projeto pretende realizar uma série de ilustrações em aquarela, baseadas em uma narrativa autoral de ficção do gênero fantasia, com a finalidade de concluir um projeto pessoal que diz respeito a dois aspectos de minha poética, dissertando assim sobre o processo criativo como escritora ilustradora, usando como referência, grandes artistas e escritores e somando a isso o desenvolvimento pessoal para a criação imagética e caracterização da obra em questão, nomeada Arpazia. O feito será possível através de uma série de estudos e experimentações técnicas, pretendendo obter como resultado uma série concisa e característica ao livro, série que futuramente será introduzida na obra final obtendo um livro com ilustrações, uma das manifestações mais tradicionais do livro infantil.
Keywords: Ilustração de livros; Aquarela; Criação (Literária, artística, etc.); Books in art